Aesthetic efficacy of resin infiltration on post-orthodontic white spot lesions using different conditioning methods: 24-month randomized control follow-up - Karaman, Emel; Alan Ünsal, Kübra; Öz, Aslıhan Zeynep; Öz, Alper Abdullah; Erçin, Özlem (EHASO, 2026)
Objectives: To assess color and fluorescence changes in post-orthodontic white spot lesions (WSLs) using different surface conditioning methods from prior to resin infiltration to a 24-month follow-up. Materials and Methods: Thirty patients, each with a minimum of four WSLs with ICDAS (International Caries Detection and Assessment System) II code 1 and 2 after bracket debonding were included. After baseline (T0), the lesions were randomly divided into four groups: regular brushing, 15% HCl (hydrogen chloride) gel, 37% H3PO4 (phosphoric acid) gel, and Er:YAG (erbium-doped yttrium aluminium garnet) laser. Icon resin infiltration was applied. In the treatment groups, color and fluorescence were reexamined just after the resin infiltration treat ment (T1), and after 6 (T2) and 24 months (T3). Results: There were no significant fluorescence or color changes between the treatment groups for the different time intervals. The control group showed a significantly lower color change from T0 to T2 and T0 to T3 than all the treatment groups whereas, at T2–T3, the control group showed the greatest improvement. Conclusions: Resin infiltration caused greater esthetic improvement and more revival of the lost fluorescence than daily brushing. HCl gel, H3PO4 gel, and Er:YAG laser are adequate conditioning methods for resin infiltration of post-orthodontic WSLs with ICDAS II code 1 and 2.
Keywords: Color stability; Fluorescence; Resin infiltration; White spot lesion